Regional career development centres for graduates in modern conditions - N. G. Vishnevskaya (Путеводитель предпринимателя)
This article proves a new organizational concept, goals and objectives of regional employment assistance centers for higher school graduates at educational institutions. Such centers shall shift the main accents from employment to recruitment, that is providing the best suiting personnel for the employer through both proper organization and correct recruitment procedures. The article proposes a new methodology for the operation of regional career development centers for the working youth and their cooperation with the regional career development centers for higher school graduates functioning on the basis of educational institutions. The concept determines the main principles in the work of educational institutions in and around graduates career development.